Answer:
2
Step-by-step explanation:
the answer is 2 ..........
we know that
in this problem we have
so
equate
substitute
therefore
rewrite as perfect square
therefore
<u>the answer is</u>
the solution set is
Answer:
x = 9
y = 13
Step-by-step explanation:
Side-Side-Side or SSS means that if all three sides of one triangle are equal to all three corresponding sides of another triangle, then the two triangles are considered to be congruent (equal).
Therefore, GH = PM ⇒ 7x + 8 = 6y - 7
and, GP = HM ⇒ 8x - 10 = 5y - 3
Rewrite the first expression to make x the subject, then substitute this into the second equation, and solve for y:
GH = PM
⇒ 7x + 8 = 6y - 7
⇒ 7x = 6y - 15
⇒ x = (6/7)y - 15/7
Substituting x = (6/7)y - 15/7 into GP = HM:
GP = HM
⇒ 8x - 10 = 5y - 3
⇒ 8[(6/7)y - 15/7] - 10 = 5y - 3
⇒ (48/7)y - 120/7 - 10 = 5y - 3
⇒ (13/7)y = 169/7
⇒ y = 13
Now we have found a value for y, substitute this into one of the expressions and solve for x:
8x - 10 = 5y - 3
⇒ 8x - 10 = (5 x 13) - 3
⇒ 8x - 10 = 62
⇒ 8x = 72
⇒ x = 9
A.......................... is the answering to this
we have
10 3/11 + 3 9/11=(10+3)+(3/11+9/11)=13+(12/11)=13=(13=(